The Relationship between Demographic Factors and Substance Craving Among Drug-Dependents - F PoorSeyedMousaiee; V Mousavi; M Kafi (Drug Control Headquarters, Research and Education Office, 2015)
Objective: This study was conducted with the aim of examining the role of demographic factors such as age, marital status, education degree, the age of initiating addiction, duration of addiction, monthly cost of drug use, and an incarceration history in the intensity of addicts' craving for substance use. Method: In this descriptive and cross-sectional study, 195 male addicts, after being interviewed, were selected as the participants of the study via convenience sampling method. They constituted six groups of opium smokers, heroin inhalers, heroin smokers, heroin injectors, methamphetamine smokers, and crack smokers and answered the questions of demographic characteristics and Franken's desire for drug questionnaire. Indeed, substance craving of the respondents was measured by the computerized test of measuring visual indicators of substance craving. Results: The results showed that there is a significant positive relationship between education degree and induced substance craving, monthly cost of drug use and induced substance craving, and also between education degree and instantaneous substance craving. Conclusion: Some demographic factors can be important factors in predicting substance craving in addicts, which is, in itself, among the significant dimensions in treatment process.